Hubungan Pelatihan Penggunaan Antropometri dengan Peningkatan Kapasitas Kader dalam Mendeteksi Stuntingdi Wilayah Kerja Puskesmas Wara, Kota Palopo: The Relationship Between Anthropometry Training and the Improvement of the Village Health Workers’ (Cadres) Competence in Detecting Stunting in Wara Public Health Centre, Palopo City - Eksanti Kadir; Resty Ryadinency; Nur Asphina R. Djano (Amerta Nutrition, 2023)
Background: Stunting is one of the chronic malnutrition health problems in children during the early growth period due to lack of nutrition given over a long time and not the adequacy of the nutrition needed. It occurs since the fetus or the First 1000 Days of Life (HPK) and will appear when the child is two years old. Objective: To determine the relationship between Anthropometry training and improving the village health workers' (cadres) competence in detecting stunting. Method: This study was quantitative observational research with a cross-sectional design. The study sample was 65 people. With the inclusion criteria, cadres are willing to become respondents and are still actively carrying out their duties as Integrated Service Post (Posyandu) cadres. A purposive sampling technique was done. The primary data were obtained from interviews through the online questionnaire and direct interviews. The bivariate analysis was a chi-square test. Result: There is a relationship between anthropometry training and the six variables studied, the namely cadre's knowledge (p=0.001), the skills of a cadre of measuring the body length of the baby (p=0.001), the skills of using micro toise (p=0.001), the skills of cadres using baby scales (p= .004), the skills of cadres using a manual scale (p<0.001), and the skills of cadres using the weight scales (p<0.001). Conclusion: The anthropometry training correlates with the knowledge of the cadres, the skills of a cadre of measuring the length of the bodies of babies, the skills of cadres using micro toise, the skills of cadres using the baby scales, the skill of cadres using a manual scale, and the skills of cadres using the weight scales in detecting stunting.